Kaedah Penerapan Ibadah dalam Kaunseling (Sains Humanika, 2012)
Ibadah (worship) is important in human life. Its importance is clearly reflected in al-Quran which explainsthat the main purpose of man’s creation is to devote himself to Allah. Realizing this, counselors see theneed to apply the element of ibadah in counseling as a method to resolve a client’s problem. Hence, thisresearch is conducted to identify methods of applying ibadah in counseling. This research is a studysurvey. Selection of sampling is by convenience method (N=30). Data is collected from questionnairesand analyzed by descriptive statistics. The research outcome shows some methods of applying the elementof ibadah in counseling such as ascertaining ibadah knowledge background of the client, identifying therelation between client’s problem with ibadah, identifying the type of ibadah suitable to be applied incounseling, identifying the counseling level suitable for applying ibadah and identifying suitablecounseling skills necessary for applying ibadah in counseling.
Keywords: Ibadah (worship); counseling; counseling level; counseling skill